Supplementation of rams with dried Acacia Saligna (Labil) H.L. Wendi. leaves improve reproductive performance without compromising carcass quality - Gebreslassie Gebru; Yayneshet Tesfay; Gurja Belay; Gebregiorgis Ashebir (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
The study aimed to provide the appropriate level of Acacia Saligna (AS) for ram supplementation that enhances their reproductive performance without compromising carcass and sensory qualities. Sixteen rams with an average initial live body weight of 21.98±1.84kg were fed ad-libitum grass hay and 200 g/d Wheat Bran (WB) with treatment diet; T1: 100; T2: 200; T3: 300; and T4: 400 g/d of air-dried AS leaves. Rams assigned on T4 had 11% and 6% higher DMI than T1 and T2, respectively, and got 5.5%, 3%, and 1.5% more CP than T1, T2, and T3, respectively. Higher impact of AS supplementation observed on development of reproductive organ on T4 than T1. The T4 rams also produced 14%, 7%, and 7.5% more semen volume and 2.5%, 2%, and 1% live sperm cell count than T1, T2, and T3 rams, respectively without jeopardizing semen quality. Furthermore, increasement of AS improved the libido and spermatozoa motility of the rams. Supplementation of AS did not produce a difference in slaughter weight, empty body weight, carcass weight, dressing percentage, and sensory quality of the rams. However, edible offal and usable product of T4 were higher than T1. The liver and kidney the most important organs were heavier in T4 than T1 rams. Hence, smallholder farmers can supplement dried AS with WB as an alternative supplement to improve the breeding efficiency of rams and produce quality meat.